Fiscal welfare, poverty and inequality - Sinfield, Adrian (Samfundsøkonomen, 2023)
Tax reliefs result in substantial losses of revenue in many countries. Their largely hidden effects tend to benefit the better-off so they can reinforce, if not increase, inequalities and undermine public spending objectives to help those in greatest need. In this article the very limited evidence on their scale and cost in taxes forgone, even less on their distributive impact, is reviewed comparatively before major effects across society of these little analysed subsidies are discussed. Indications of fiscal policies that could contribute to tackling the trends that contribute to higher poverty and inequality are briefly outlined.